Algunas reflexiones y propuestas acerca del Prácticum en la especialidad de educación Física mediante un grupo de discusión - Cipriano Romero Cerezo; María del Mar Ortíz Camacho (Universidad de La Rioja, 2013)
The present work deals with teacher training practice in Physical Education. For this we have used the technique of discussion groups. Such a group was made up of 10 teachers-tutor, students, and university supervisors who met at two different periods of time. The discussion sessions were transcribed, categorized and grouped around three major categories to be analysed. Such an analysis included a count of frequencies of the categories and their interpretation. Finally we propose some ways to improve this type of practice.